Failure analysis of tube-to-tubesheet welded joints in a shell-tube heat exchanger. (October 2016) - Liu, Long; Ding, Ning; Shi, Junbo; Xu, Na; Guo, Weimin; Wu, Chi-Man Lawrence
Highlights: Fatigue failure of welded joints in a shell-tube heat exchanger was analyzed. Fatigue crack initiated from the defects at the tube-to-tubesheet welded joint. Bad welding and unsuitable expansion gave rise to the formation of initial cracks. The alternating stress comes from various reasons such as the resonant vibration. Abstract: Failure analysis was carried out on a tube-to-tubesheet welded joint of a shell-tube heat exchanger to confirm its failure mechanism. The collected evidence suggests that the failure of the tube-to-tubesheet welded joint was induced by fatigue. Under the morphology analysis, the fracture surface exhibit obvious fatigue crack propagation traces. Fatigue striations were observed clearly in the propagation zone. Detecting results showed that chemical composition and mechanical properties of the tubes was consistent with the standard requirements for the 304 stainless steel. The metallographic test showed that the microstructure of both the tube and tubesheet were normal. However, serious defects were found at the tube-to-tubesheet welded joint. The fatigue crack initiated from the defects at the tube-to-tubesheet welded joint. The periodic load might come from the resonant vibration of the tube or the changes in temperature and pressure of the fluid inside the heat exchanger. Bad welding and unsuitable expansion position of the tubes at the tube-to-tubesheet might give rise to the formation of initial cracks.